Analisis Hukum Tanggung Jawab Marketplace Lazada Atas Pembekuan Akun dan Saldo Penjualan Berdasarkan PP Nomor 80 Tahun 2019 - Asep Setiawan; Ahmad Nurun (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This research analyzes the legal responsibility of marketplace operator Lazada regarding the freezing of seller accounts and sales balances based on Government Regulation Number 80 of 2019 concerning Trade Through Electronic Systems. Using a qualitative juridical empiric approach, the study examined the case of Aba Mart, a seller who experienced account freezing and loss of approximately Rp 15 million in sales balance. Through in-depth interviews, direct observation, and documentation analysis with Aba Mart as the single case subject, the research reveals that Lazada's unilateral account freezing actions constitute breach of contract and unlawful conduct, violating Articles 7, 15, and 18 of PP No. 80/2019. The findings indicate that Lazada violated the principles of good faith and balance in the Indonesian Civil Code. The dispute resolution mechanisms available to sellers prove ineffective and inaccessible, particularly for small traders in Bandung. This research recommends comprehensive regulatory reforms addressing transparency standards, independent appeal mechanisms, strengthening of standard contract clauses, and provision of legal assistance to small business operators to create a fair and equitable e-commerce ecosystem.